Role of the Pruritic Cytokine IL-31 in Autoimmune Skin Diseases - Gibbs, Bernhard F.; Patsinakidis, Nikolaos; Raap, Ulrike (Frontiers in Immunology, 2019)
Many autoimmune skin diseases, such as bullous pemphigoid (BP), psoriasis and certain types of chronic urticaria, are associated with intensive pruritus. While histamine and neuropeptides have previously been ascribed to play a role in itch that accompanies these diseases, recent evidence suggests that the pruritogenic cytokine interleukin (IL)-31 is a major driver of pruritic responses. IL-31 was originally shown to be produced by activated helper T cells, particularly Th2 cells, mast cells, macrophages and dendritic cells. However, more recent evidence demonstrated that eosinophils are a major source of this cytokine too, particularly in bullous pemphigoid. Basophils have also been shown to express the cytokine which, through autocrine action, strongly supports the production of other Th2-type cytokines from these cells. These investigations suggest that the dynamic recruitment of eosinophils and basophils in some autoimmune skin diseases could play an important role in the severity of IL-31-mediated itch. Furthermore, these studies suggest that IL-31, in addition to its pruritic actions, also has potential immunomodulatory roles in terms of supporting Th2-type immunity, which often underpins IgE-associated autoimmune diseases (such as bullous pemphigoid and urticaria) as well as allergies. While the role of IL-31 in psoriasis remains to be clarified, current evidence shows that this cytokine plays a major role in BP, chronic spontaneous urticaria and dermatomyositis. This suggests potential use of IL-31 receptor-blocking therapeutic approaches (e.g., Nemolizumab) for the treatment of IL-31-associated disorders.